PERAN KOMPETENSI SOSIAL GURU DALAM MENCIPTAKAN LINGKUNGAN BELAJAR YANG INKLUSIF PADA SISWA KELAS IV UPTD SDN ASAM TIGA KABUPATEN KUPANG - Mona, Grasella Yulianti; Kristina E. Noya Nahak; Cornelia Amanda Naitili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Every student has different backgrounds, abilities and needs. Therefore, it is important for teachers to have good social competence in order to create an inclusive learning environment - an environment that accepts, respects and provides a fair learning space for all students. However, in practice, teachers often face obstacles in building a friendly and equal classroom atmosphere. This study aims to find out the role of teachers' social competence in creating an inclusive learning environment, as well as the challenges faced in the process. This study used a descriptive qualitative approach, with data collection techniques in the form of interviews, observation and documentation. The research subjects were fourth grade teachers, principals, and fourth grade students of UPTD SDN Asam Tiga, Kupang Regency. The results showed that teachers have implemented social competence through good communication with students and parents, establishing cooperation with colleagues, and starting to engage in self-development through professional networks. However, teachers also face challenges, such as limited facilities, lack of training, difficulty adjusting learning strategies to the needs of diverse students, and obstacles in building positive interactions between students. It can be concluded that teachers' social competence plays an important role in creating an inclusive learning environment even though the implementation still faces various challenges. Support from schools and government is needed to overcome these challenges.